Evaluating the impact of Carbon Emission Trading Policy on pan-cancer incidence among middle-aged and elderly populations: a quasi-natural experiment - Chuang Yang; Yiyuan Sun; Yihan Li; Lijun Qian (Environmental Health and Preventive Medicine)
Background: Cancer is a major public health concern, particularly among middle-aged and elderly populations, who are disproportionately affected by rising cancer incidence. Environmental pollution has been identified as a significant risk factor for cancer development. China’s Carbon Emission Trading Policy (CETP), implemented in pilot regions since 2013, aims to reduce carbon emissions and improve air quality. This study evaluates the impact of CETP on pan-cancer incidence, with a focus on its effects on specific cancer types and vulnerable populations. Methods: This quasi-natural experiment utilized data from the China Health and Retirement Longitudinal Study (CHARLS) and environmental data from the China National Environmental Monitoring Center (2011–2018). A staggered difference-in-differences (DID) model was employed to estimate the impact of CETP on cancer incidence. Robustness tests, including parallel trend tests, placebo analysis, and entropy balancing, validated the findings. Subgroup analyses were performed to assess the policy’s heterogeneous effects based on gender, Body Mass Index (BMI), and smoking status. Results: CETP implementation significantly reduced the incidence of six cancer types: endometrial, cervical, gastric, esophageal, breast, and lung cancers. Overall, pan-cancer incidence significantly declined post-policy implementation (CETP × POST: −47.200, 95% CI: [−61.103, −33.296], p < 0.001). The policy demonstrated stronger effects in highly polluted areas and among individuals with poorer mental health. Subgroup analysis revealed that females, individuals with lower BMI, and non-smokers experienced more substantial benefits. Conclusions: CETP significantly reduces cancer incidence by improving environmental quality and influencing mental health, with particularly strong effects observed among high-risk populations. This study highlights the important role of environmental economic policies in mitigating cancer burden and promoting public health. Future research should further explore the long-term impacts of this policy and its applicability across different national and regional contexts.